THE 21st CENTURY CLASSROOM TEACHERS’ READINESS TOWARDS THE USE OF EKO EXCEL HANDHELD TECHNOLOGY IN PUBLIC PRIMARY SCHOOLS - OLUJUWON, TOLA; BAMIRO, NURUDEEN B.; AKUDO, KENNEDY O.; ANAGUN, ADEYEMI M.; ANAGUN, ADEYEMI M. (Sokoto Educational Review, 2022)
This study assessed teacher readiness in the use of Eko Excel handheld technology in teaching and learning in public primary schools in Lagos State, Nigeria. The population of the study comprised public primary school teachers in Lagos who were given a handheld Eko Excel tablet for use in their classrooms and adopted the descriptive survey with partly structured and unstructured questionnaires on Google form. Data were analysed using the Likert scale, tables, and bar charts. Findings from the study reveal that teachers were ready for the use of ICT in the classroom as it enhances classroom instruction and shows their level of productivity. The study further reveals that there are technical issues that affect the workability of the device. The study recommends upgrading content delivery in line with local realities. Also, technical issues that hamper the workability of the device should be tackled on time in other for excellent performance.